Fatigue Damage Estimation in Existing Railway Steel Bridges by Detailed Loading History Analysis. (24th July 2012) - Pipinato, Alessio; Pellegrino, Carlo; Modena, Claudio
Abstract : Fatigue life estimation of metal historical bridges is a key issue for managing cost-effective decisions regarding rehabilitation or replacement of existing infrastructure. Because of increasing service loads and speeds, this type of assessment method is becoming relevant. Hence there is a need to estimate how long these structures could remain in service. In this paper a method to estimate fatigue damage in existing steel railway bridges by detailed loading history analysis is presented. The procedure is based on the assumption that failure probability is a function of the number of predicted future trains and the probability of failure is related to the probability of reaching the critical crack length.